Berlusconism – Manipulation in Italian Media of the 1980s - Jaworska, Beata (The phenomena of propaganda and manipulation in the press, radio, television, and internet. Volume III, 2025)
The aim of this article is to identify and discuss the manipulative tools used by the Italian media in the 1980s. It is possible by following the activities of Silvio Berlusconi – a figure who played an important role in the media and political world of those years and whose decisions still shape Italian reality. Particular attention was paid to the phenomenon of boom economico and its impact on Italian television in the second half of the 20th century, as well as the manipulative tools thanks to which Berlusconi managed to influence the system of values and worldview of Italians in the long term. The review character of the article, focusing on the analysis of Italian- and Polish-language scientific texts devoted to the spectacularization of the media, their history, and the issue of the figure of the woman in the media environment of  that time, allows for the identification of the connection between the figure of the Italian viewer and the figure of the Italian voter, showing the enormous degree of influence and intertwining of the two most important spheres of public life of the inhabitants of the Apennine Peninsula at that time – television and politics.